2002
DOI: 10.1080/00015550252948130
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Prevalence of Arthritis Reported by 5,795 Members of the Nordic Psoriasis Associations

Abstract: Quality of life measures are widely used in dermatology as well as in rheumatology, but there are no large studies taking arthritis into consideration when studying quality of life in psoriasis. The aim of this study was to investigate psoriasis-related quality of life in a large sample of members of the psoriasis associations from the Nordic countries including an arthritis-related evaluation. The prevalence of reported arthritis within the groups was also estimated. An Arthritis Disability Index suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
2
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(163 citation statements)
references
References 0 publications
4
148
2
9
Order By: Relevance
“…Many patients have erosive disease, physical limitations, and work-related disability 22,24 . Patients with PsA may experience more pain and more role limitations than patients with RA 25,26 and patients with psoriasis alone 27,28 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Many patients have erosive disease, physical limitations, and work-related disability 22,24 . Patients with PsA may experience more pain and more role limitations than patients with RA 25,26 and patients with psoriasis alone 27,28 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Social exclusion, discrimination and stigma are psychologically devastating for individuals suffering from psoriasis and their families. Psoriasis affects relationships at home, school and work as well as sexual relationships and thus reduce QoL and adds to the social and psychological strain (19,20) . Moreover, the chronic recurrent nature of the disease, the erythema and scaliness lead to the hopelessness of complete cure to its treatment and have a great impact on patient self-esteem and confidence and reported cases of suicidal attacks (21)(22)(23) .…”
Section: Introductionmentioning
confidence: 99%
“…The patient-perceived effect of PsA has been usually assessed through generic questionnaires such as the HAQ or short form 36. [10][11][12]27 VITACORA-19 disease-specific instrument has been developed to evaluate HRQoL in patients with PsA and the objective was to develop a questionnaire to calculate a score reflecting the effect of PsA based on patients' perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced functional capacity and QoL are expected outcomes of PsA. [10][11][12] Self administered Psoriatic Quality of Life (PsQoL) scale was developed to evaluate the QoL of patients with PsA. 13 A validity study for the Turkish version of PsQoL was performed by Duruöz et al, 14 who demonstrated PsQoL to be relevant and acceptable to respondents, valid, and reliable with proven sensitivity to changes.…”
mentioning
confidence: 99%